Conducting mixed-methods research with Ebola survivors in a complex setting in Sierra Leone - Soumya Alva; Nicole Davis; Laurentiu Stan; Isotta Pivato; Jeffrey Sanderson (BMC, 2020)
Abstract Background In late 2015, the Sierra Leone government established the Comprehensive Program for Ebola Survivors (CPES) to improve the well-being of 3466 registered Ebola virus disease (EVD) survivors. This case analysis outlines the challenges of conducting research studies on the health situation of these EVD survivors in a complicated, post-Ebola context. It outlines strategies to address these challenges without compromising research quality. The mixed-methods study sought to determine EVD survivors' access to health services offered through CPES, their health and disability status, and psychosocial and mental health issues faced. Qualitative data from survivors and stakeholders at multiple levels complemented and contextualized the survey results to help understand the unique health and associated socioeconomic challenges that EVD survivors face, which could be applied to other crisis settings. Study findings indicated that CPES had lasting impacts on Sierra Leone's health system, enabling it to respond to EVD survivors, who increasingly accessed health services and showed lower levels of disability after receiving care. Discussion Understanding the health service needs of this specialized population in a country with an overloaded health system after the Ebola epidemic makes this research study important and timely. The study faced several challenges, including working in a low-resource and low-capacity setting marked by constantly changing priorities and activities of CPES donors and implementers. Further, the study aimed to measure sensitive topics, such as mental health and disability, with standardized tools that required careful contextualization for accurate reporting of findings. Strategies to overcome these challenges included utilizing a mixed-methods approach to contextualize and validate survey results. The study also enabled capacity building of local research teams to ensure that they could follow lines of inquiry and navigate the complex post-Ebola context. Conclusions Flexibility is paramount when conducting high-quality research for representative and useful results. Timely research and ongoing sharing of the findings with stakeholders is critical to ensure that they benefit study subjects. Furthermore, in such settings, there is a need to balance engagement of stakeholders with maintaining independence and impartiality in the research design and subsequent data produced.